El nuevo regionalismo y el Consejo de Defensa Suramericano - Serbin Pont, Andrei [UNESP] (2014)
The Southamerican Defense Council (CDS) is one of the most recent regional initiatives aimed at fostering defense integration in South America. It arises in the context of a multilateral organization of regional reach, UNASUR, that exemplifies many of the distinctive characteristics of the integration processes of the postliberal and/or posthegemonic regionalism period. The CDS aims at consolidating a series of objectives in matters of defense that correspond with this phase of regionalism, breaks traditional paradigms of importing and/or imposing extraregional models and seeks to implement solutions based on regional idiosyncrasy. In the framework of the creation of the CDS we analyze the integration mechanisms in matters of defense and the structures being developed in South America in the context of regional and subregional experiences that impact on the configuration of this particular council.